Information Asymmetry, Shortage of Liquidity and Evidence on the Role of Credit Sales in Business-to-Business Marketing - Karakoç, Bahadır (Sage Publications Ltd, 2022)
This study explores the role of credit sales in the context of business-to-business marketing using publicly traded firm data from nine developed economies and the panel data methodology. The findings indicate that offering trade credit is not a substitute for traditional marketing; on the contrary, it complements it. As the need for marketing increases, firms offer more trade credit, and this is particularly the case for those with information asymmetry. Finally, liquidity-poor firms rely more on credit sales to support marketing. The findings overall suggest that firms, particularly the ones with information asymmetry, and lack of liquidity, can utilize trade credit in achieving marketing-related goals in a business-to-business setting.
Keywords: Trade credit; marketing expenses; asymmetric information; liquidity; Trade Credit; Financial Crisis; Determinants; Performance; Quality; Model